Oral Candidiasis Management in a Child with Pacifier Sucking Habit: A Case Report - Nuraeni Hartati; Anrizandy Narwidina; Sri Kuswandari (Universitas Sam Ratulangi, 2024)
Abstract: Oral candidiasis is a widely known mucosal fungal infection caused by an overgrowth of Candida species. Children and infants are highly more susceptible to Candida infection than adults. We report an oral candidiasis case in a 5-year-old girl with white spots on her lips and tongue. When the white spots were scrapped off, they would be detached leaving red patches on the mucosal surfaces. The patient had pacifier sucking habit and tended to place the pacifier everywhere carelessly. Previously, the patient was treated at a primary healthcare center and received nystatin therapy. However, there was no improvement at all after the therapy. Based on her current and historical conditions, the patient was diagnosed as oral candidiasis, and in this case nystatin administration was ineffective. Therefore, the patient required better oral hygiene management, and the medication given was a gargle containing 0.1% hyaluronic acid. A week after using the gargle without using pacifier anymore, white spots had disappeared, and oral hygiene had improved. Re-control was conducted one month after the first visit and no Candida infection was detected. In conclusion, gargle containing 0.1% hyaluronic acid associated with better dental and oral hygiene is effective to treat oral candidiasis in children. Keywords: oral candidiasis; children; pacifier sucking habit; gargle containing 0.1% hyaluronic acid